Impementasi Model Pembelajaran Kooperatif dalam Meningkatkan Kerjasama antara Siswa Kelas V SDN 30 Mataram - Ratul; Muntarir; Muharrar, Ahmad (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to describe the implementation of cooperative learning models intended to enhance collaboration among fifth-grade students at SDN 30 Mataram, as well as to identify the challenges faced by teachers during the implementation process. The research employed classroom action research (CAR) with a descriptive qualitative approach. Data were collected through observations, interviews, and document analysis. The findings indicate that cooperative learning models, such as Jigsaw and Think-Pair-Share, are effective in improving student interaction and collaboration. Students became more actively engaged in group discussions, shared ideas with one another, and worked collaboratively to complete tasks. However, several obstacles were encountered in the implementation of cooperative learning models, including: (1) students’ social discomfort; (2) the dominance of certain students within groups; (3) difficulties in designing tasks aligned with cooperative learning models; and (4) differences in students’ abilities. Therefore, appropriate strategies are required to ensure that cooperative learning models can be optimally implemented to enhance student collaboration.